Synthetic applications of samarium(II) iodide mediated regioselective cleavage of phenylsulfonyl activated cyclopropyl ketones - Vichai Reutrakul (2018)
Reductive cleavage of phenylsulfonyl activated cyclopropyl ketones with samarium(II) iodide led regioselectively to samarium enolates or dienolates. These were trapped with some alkylating agents.